1997
DOI: 10.1046/j.1471-4159.1997.68010068.x
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrophin Protection Against Toxicity Induced by Low Potassium and Nitroprusside in Cultured Cerebellar Granule Neurons

Abstract: Long‐term survival of cultured rat cerebellar granule neurons requires depolarizing concentrations of potassium (high potassium; 25 mM KCl). A high‐potassium culturing condition has been reported to increase the intracellular calcium concentration ([Ca2+]i) and the expression of brain‐derived neurotrophic factor (BDNF), which in turn induces the expression of neurotrophin‐3 (NT‐3) in these neurons. We therefore examined the neurotrophic effect of these two neurotrophins in low‐potassium (5 mM) cultures and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…NT‐3 is a neurotrophic factor that has been extensively studied for its neuroprotective potential, and even though its mechanism of action is not fully understood it has been suggested that NT‐3 exerts direct effects on neurons subjected to oxidative stress or exposed to neurotoxic substances (Yu and Chuang, ; Korsak et al, ; Ma et al, ). Inflammation, hypoxia, and excitotoxicity are conditions likely to be present in SCSC following culture preparation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NT‐3 is a neurotrophic factor that has been extensively studied for its neuroprotective potential, and even though its mechanism of action is not fully understood it has been suggested that NT‐3 exerts direct effects on neurons subjected to oxidative stress or exposed to neurotoxic substances (Yu and Chuang, ; Korsak et al, ; Ma et al, ). Inflammation, hypoxia, and excitotoxicity are conditions likely to be present in SCSC following culture preparation.…”
Section: Discussionmentioning
confidence: 99%
“…Neurotrophin (NT)‐3 is a neurotrophic factor that has been extensively studied for its neuroprotective effects (Ma et al, ; Yu and Chuang, ). Briefly, NT‐3 enhances neuronal survival of mechanically injured neurons in vitro (Ma et al, ) and improves neurological recovery followed ischemic brain damage in vivo (Zhang et al, ).…”
mentioning
confidence: 99%